Bed Bug, Cimex lectularius Linneaus (Insecta: Hemiptera: Cimicidae) - Shawn E. Brooks (EDIS)
This document provides a comprehensive profile of the bed bug, Cimex lectularius, detailing its biology, distribution, and management. Bed bugs are blood-feeding parasites found in human dwellings, bird nests, and bat caves. They are active mainly at night and can be transported via clothing and luggage. The document covers identification features, life cycle, and signs of infestation. Management strategies include sanitation, mechanical methods, and cautious use of pesticides. Despite their potential to carry diseases, bed bugs have not been implicated in disease transmission to humans. Published: June 2000.